SLIPPERY SLOPE FRAMEWORK: MOTIVASI PEMBAYARAN PAJAK DAN KEPATUHAN PAJAK - Amalia, Firda Ayu (Jurusan Akuntansi Fakultas Ekonomi Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
The purpose of this study is to provide empirical evidence behind tax compliance based on a slippery slope framework, namely the motivation to pay taxes due to the power (power) of the government or the awareness of the taxpayers themselves.Â This study uses a quantitative descriptive approach with data collection techniques in the form of questionnaires and interviews. The sample used was the UMKM actors in Batu's city with a purposive sampling technique. The study results provide empirical evidence that tax payment motivation has a positive effect on tax compliance. Furthermore, interviews with several MSME actors who became respondents stated that tax payments were based on the government's power. It can be said that the motivation for tax payments has not been based on the taxpayer's awareness. The research results are expected to provide advice to the government regarding policies or steps that should be taken to increase the trust (trust) of taxpayers on tax payments that have been made. If the trust is built, tax compliance can increase without coercion.